HISTORY, SOCIETY AND THE PHENOMENON OF CULTISM IN OUR INSTITUTIONS OF LEARNING: IMPLICATION FOR COUNSELING - Saulawa, A. M. (Sokoto Educational Review, 2020)
Considering the preponderance of turbulence owing to cultism in our educational institutions in recent years, it is significant that the root causes of such destabilizing factor is thoroughly investigated and informed to educational administrators and other policy-makers to utilize by precluding or at least limiting further its occurrence. Hence, the main thrust of the paper therefore, is to examine historically the causes and effects of cultism in Nigerian Institutions of learning with a view to showing its implications for counselling our society, which is today ridden with a lot of socio-political and economic problems.